STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA PAKUBUEAN TAGAK DI KAMPUANG TANJUANG MALAI V SUKU KECAMATAN BATANG GASAN KABUPATEN PADANG PARIAMAN - Salsabila, Riri; WS, Hasanuddin; Nasution, Muhammad Ismail (Jurnal Bahasa dan Sastra, 2018)
This study aimed to describe the structure and social function of folklore Pakubuean Tagak legend in Kampuang Tanjuang Malai V tribal district Batang Gasan Padang Pariaman. This study is a qualitative research with descriptive methods that describe the data contained in the object of research, the theory used, data analysis, and so on. To find out the structure and social function of the folklore of Pakubuean Tagak legend researchers conducted a study by interviewing several informants who knew the story. This research was located in Kampung Tanjuang, Batang Gasan District, Padang Pariaman District. This research was conducted in several stages: (1) recording stage then transcribed the data and transliterated the data. (2) classifying data based on the theory that has been determined. Based on the results of the study of folklore structure, The first is the structure of folklore Pakubuan Tagak legend contained in Kampuang Tanjuang Nagari Malai V Suku District Batang Gasan Padang Pariaman District. The second conclusion was that the folklore of the Pakubuan Tagak legend found in the Tanjuang Nagari Malai V Kampong, Batang Gasan Subdistrict, Padang Pariaman District has a social function as a means of entertaining and educatingKeywords: Social Function, Folklore, Legends